Cilioretinal Arteries in Highly Myopic Eyes: A Photographic Classification System and Its Association With Myopic Macular Degeneration - Meng, Jiaqi; Wei, Ling; Zhang, Keke; He, Wenwen; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2020)
Purpose: To develop a photographic classification for cilioretinal arteries and to investigate its association with myopic macular degeneration (MMD). Methods: 1692 highly myopic eyes of 1692 patients were included. The presence of a cilioretinal artery was determined by fundus photographs, and a photographic classification was proposed. MMD was classified according to the International META-PM Classification. Associations of the cilioretinal artery and its classifications with MMD and visual acuity were analyzed. Results: Of the eyes tested, 245 (14.5%) had a cilioretinal artery. The cilioretinal arteries were classified into four categories (temporal “cake-fork”, 35.92%; temporal “ribbon”, 53.47%; “multiple”, 6.53%; “nasal”, 4.08%) and 3 distributions based on whether its visible branches reached the central foveal area. Eyes with cilioretinal arteries had significantly less MMD of grade ≥ 3 and better visual acuity than those without (P<0.01). Multiple linear regression analysis showed that younger age, male sex, shorter axial length, and the presence of a cilioretinal artery were associated with better visual acuity in highly myopic eyes (all P<0.05). The “nasal” category presented more MMD with grade ≥ 3 and worse visual acuity than the other categories (P<0.05), whereas the “multiple” category contained no eyes with MMD grade ≥ 3. The cilioretinal arteries reaching the central foveal area showed less MMD of grade ≥ 3 and better visual acuity than those not (P<0.05). Conclusions: We propose a photographic classification for cilioretinal arteries that has good clinical relevance to visual functions. The cilioretinal artery may potentially afford protection against MMD.